Pengaruh Corporate Social Responsibility Terhadap Financial Performance, Firm Value, Dan Share Price Perusahaan Industri Ekstratif (Jurnal Paradigma Akuntansi, 2022)
The purpose of this study is to obtain empirical evidence about the effect of corporate social responsibility on financial performance, Firm Value and Share Price in extractive companies listed on the Indonesia Stock Exchange (IDX) for the 2017–2019 period. The research is conducted by taking 36 samples using purposive sampling method. Data processing technique uses simple regression analysis assisted by the SPSS (Statistical Product and Service Solution) program for Windos released 25 and Microsoft Excell 2013). The t test results indicate that corporate social responsibility (CSR) has a positive but insignificant effect on financial performance and firm value, while corporate social responsibility (CSR) has a significant and negative effect on share price. The implication of this study is that there is a need for an increase in corporate social responsibility to improve firm performance and firm value.